Expression of HLA‐DRA and CD74 mRNA in whole blood during the course of complicated and uncomplicated Staphylococcus aureus bacteremia. (12th October 2017) - Rasmussen, Gunlög; Cajander, Sara; Bäckman, Anders; Källman, Jan; Söderquist, Bo; Strålin, Kristoffer
ABSTRACT: To improve management of Staphylococcus aureus bacteremia (SAB), better understanding of host–pathogen interactions is needed. In vitro studies have shown that S. aureus bacteria induce dose‐dependent immunosuppression that is evidenced by reduced expression of major histocompatibility complex (MHC) class II on antigen presenting cells. Thus, the aim of this study was to determine whether expression of the MHC class II‐related genes HLA‐DRA and CD74 is more greatly reduced in complicated SAB, with its probable higher loads of S. aureus, than in uncomplicated SAB. Adult patients with SAB were prospectively included and blood samples taken on the day of confirmation of SAB (Day 1) and on Days 2, 3, 5 and 7. HLA‐DRA and CD74 mRNA expression was determined by quantitative reverse transcription PCR. Sepsis was defined according to the Sepsis‐3 classification and SAB was categorized as complicated in patients with deep‐seated infection and/or hematogenous seeding. Twenty patients with SAB were enrolled and samples obtained on all assessment days. HLA‐DRA and CD74 expression did not differ significantly between patients with SAB and sepsis ( n = 13) and those without sepsis ( n = 7) on any assessment day. However, patients with complicated SAB ( n = 14) had significantly weaker HLA‐DRA expression on all five assessment days than patients with uncomplicated SAB ( n = 6). Additionally, they tended to have weaker CD74 expressions. Neutrophil, monocyte and leukocyte counts did not differ significantly between complicated and uncomplicated SAB. In conclusion, patients with complicated SAB show weaker HLA‐DRA expression than those with uncomplicated SAB during the first week of bacteremia.